Cold Chain Improvement in Network Perspective - Xing, Xiaoyue (2017)
With the development of economics and technology, the demands of consumption of temperature-sensitive products, such as fruits, flowers, drugs, dairy drinks and etc, and the needs of transporting these perishables product regionally or even globally increase dramatically. The cold chain makes it possible to preserve the value of products as keeping the quality of perishables goods until the point of customers and extending the life cycle to avoid value losing. The cold chain also adds value since it transforms the products to the market where they are considered with higher values. However, issues and challenges, including high cost, pollution, lack of power and facilities, the shortage of training and control, block the development of global cold chains. To improve the status the cold chain, many researchers come up with several methods and ideas but rare studies using the perspective of the network to increase the effectiveness and efficiency of the performance of the cold chain. The author will classify the types of networks according to the participants and utilize the theory of supply chain network and personal network to explore possible ways to benefit both academic and industry of cold chain. In the perspective of supply chain network, the multi-modal transportation mode can reduce the direct handling of products. The training and education on the participants of the industry can increase the efficiency of utilization of refrigeration facilities. And the risk management through the whole chain networks can reduce the possibility of failure and loss. In the perspective of the personal network, the knowledge and technology flow within the network can improve the research level and practical experience. And the linkage provided by the network between academics and industry promotes the generation of new ideas and application of best practices. Therefore, the Global Cold Chain Network, founded by Prof. Kulwant Pawar, connects academic institution and industrial companies located in more than fifteen countries and regions to encourage the information flowing and experience sharing between universities and organizations which will highly benefit the global improvements in the cold chain.